LEGAL CONSIDERATIONS OF THE PUBLIC PROSECUTOR'S OFFICE OF THE REPUBLIC OF INDONESIA AS A MEANS OF PREVENTING CORRUPTION IN THE DIVESTMENT PROCESS OF STATE-OWNED ENTERPRISES - Eko Setiawan (2021)
Many parties believe that through preventive efforts by law enforcement officials, corruption can be eradicated from Indonesia and the prosecutor's office can carry it out with the function of legal considerations. Currently this function is carried out in a limited manner, although regulations do not limit it. State-owned enterprises desperately need the authority of the prosecutor's office. They need a legal opinion that can protect them from potentiao violations of the law. The researcher used the normative juridical researce method and concluded that the legal considerations carried out by the prosecutor required the existence of a broad legal analysis factor from professional personal in order to be a means of preventing corruption.Efforts to optimize legal considerations can be made by expanding the scope of regulations related to the provision of legal considerations other than civil and state administration and efforts to prevent criminal acts of corruption